2024
DOI: 10.3389/fimmu.2024.1346035
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota-gonadal axis: the impact of gut microbiota on reproductive functions

Victory J. Ashonibare,
Bolaji A. Akorede,
Precious J. Ashonibare
et al.

Abstract: The influence of gut microbiota on physiological processes is rapidly gaining attention globally. Despite being under-studied, there are available data demonstrating a gut microbiota-gonadal cross-talk, and the importance of this axis in reproduction. This study reviews the impacts of gut microbiota on reproduction. In addition, the possible mechanisms by which gut microbiota modulates male and female reproduction are presented. Databases, including Embase, Google scholar, Pubmed/Medline, Scopus, and Web of Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 198 publications
0
2
0
Order By: Relevance
“…In another study, the inoculation of certain strains of Lactobacilli in female mice led to changes in serum levels of estrogen and testosterone [165]. The relationship between testosterone and gut microbiota is intricate; testosterone alters the composition of gut microbiota, and, at the same time, gut microbiota also influences the production of testosterone [166]. Marlke et al demonstrated that, after microbiota transplantation, there was an increase in circulating testosterone levels.…”
Section: Brain-gut Microbiota Axis and Sex Differencesmentioning
confidence: 99%
“…In another study, the inoculation of certain strains of Lactobacilli in female mice led to changes in serum levels of estrogen and testosterone [165]. The relationship between testosterone and gut microbiota is intricate; testosterone alters the composition of gut microbiota, and, at the same time, gut microbiota also influences the production of testosterone [166]. Marlke et al demonstrated that, after microbiota transplantation, there was an increase in circulating testosterone levels.…”
Section: Brain-gut Microbiota Axis and Sex Differencesmentioning
confidence: 99%
“…Metagenomic investigation of the chicken reproductive microbiome has arisen as a new area of study, providing insight into the relationships between host genetics, microbiota composition, and reproductive health. We can investigate the role of the microbiome in regulating fertility, disease resistance, and immunological responses in chickens by identifying the microbial populations in the reproductive tract [ 18 ]. Metagenomics has implications for developing techniques to modify the microbiome for better reproductive health [ 19 ].…”
Section: Introductionmentioning
confidence: 99%